DEFINING EFFECTIVE CONTROL UNDER THE LAW OF OCCUPATION AFTER ISRAEL’S DISENGAGEMENT PLAN 2005 - Evan Tobias (International Law Department, Faculty of Law Universitas Padjadjaran, 2021)
During the conflict between Israel and Palestine, Israel had occupied Palestinian territory. In 2005, Israel issued the Disengagement Plan, which led Israel to declare that they no longer had any legal obligation to administer the Gaza area as an Occupying Power. In this regard, Israel’s declaration is based on the Plan which governed their withdrawal from Gaza, followed by the recognition of Palestine’s authorities. However, the situation regarding Israel's occupation status on the ground said otherwise. This paper will analyze whether the Disengagement Plan revokes the status of Israel as an Occupying Power and thus Israel has no longer obligations toward the Occupied Territory. By analyzing the constitutive elements of belligerent occupation and comparing them with the factual condition, this paper found that Israel should be regarded as an occupying power over the territory of Gaza. Moreover, even though Israel rejects its status as occupying power, Israel is still obligated to comply with the applicable law of armed conflict.